Impact of Industry 4.0 and circular economy on lean culture and leadership: Assessing digital green lean as a new concept - Ignacio S. Gatell; Lucia Avella (European Research on Management and Business Economics (ERMBE), 2024)
This paper aims to investigate the impact of Industry 4.0 and Circular Economy on Lean Leadership and Lean Culture, providing insights into how Lean Manufacturing companies can adapt their leadership and culture styles to succeed in the new business environment. We have conducted a systematic literature review focusing on the impact of Industry 4.0 and Circular Economy on Lean Leadership and Lean Culture, and our principal findings are that Implementing Industry 4.0 and Circular Economy requires changes in Lean Leadership and Culture styles to incorporate sustainability and digital transformation. This study identified ten Lean Culture characteristics classified in three groups values and principles (culture of respect, collectivism, power distance and authority distribution), customer centric (customer orientation and performance orientation) and operational excellence (receptiveness, working conditions, problem solving culture and continuous improvement and innovation) and nineteen Lean Leadership competences grouped in three categories customer oriented (customer focus, customer and supplier development and teamworking), personal development (personal stability, personal behavior, human centric, self-developing and learning, empowerment, self-transcendence and servant leadership), Lean principles (experimental, continuous improvement and innovation, zero-defects, process and lean expertise, problem solving and genchi genbutsu) and performance driven (targets settings, targets deployment and flow) that are necessary for successful implementation of Industry 4.0 and Circular Economy in Lean Manufacturing companies.
Keywords: M11; M14; M15; M12; 650; Circular economy; Industry 4.0; Leadership; Lean culture